Mobile semantic data exchange in ad hoc networks using distributed profiles - Baumgart, André; Knapp, Hartwig; Schader, Martin (1st International Symposium on Wireless Pervasive Computing, 2006, 2006)
Collecting relevant information from a heterogeneous set of data resources is a challenging problem. Moreover, the storage and search for semantic data is even more complex in mobile environments. In this paper we present an approach how to collect semantic information by underlying profile settings. We define several profile types and levels where the user's interests are stored. Information retrieval is then executed according to the profile settings. Distributed profiles for mobile semantic data exchange can personalize the exchanged information in business settings. This leads to effective data transmission with regard to the mobile (device) context and the business environment, the user is exposed to. Our realization of a prototype confirms the effective semantic data exchange. The evaluation of dynamic profile settings in ad hoc network scenarios verifies our approach experimentally.